Literature Reviews: Unwanted Pregnancy in Adolescents and Factors that Influence - Noveri Aisyaroh; Machfudloh Machfudloh; Safarina Qurota A'Yunida (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The impact of free sex behavior is the occurrence of Unwanted Pregnancy (KTD), this phenomenon is still rife in Indonesia. KTD reached 17.5% which means it is quite high in 2020, which is caused by various factors; parenting patterns, lack of knowledge, easy access to pornographic media, attitudes of close friends towards sexuality, lack of religious attitudes, age, living without permissive parents, low socioeconomic status, and teenagers who do not go to school. Purpose: to find out the factors that influence adverse events based on the latest evidence based on various articles. Methods: The design used is a literature review, the articles are collected using 2 based data, namely google schoolar, pubmed, ebsco, and the google schoolar search engine. The article search results obtained 20 articles, namely Google schoolar 10 articles, pubmed 5 articles, and Ebsco 5 articles. The criteria for the articles used are original articles, published for 10 years (2011 – 2021), full text and free access. There are 6 articles that meet the inclusion criteria, namely the factors causing unwanted pregnancy in adolescents. Results: Based on the articles collected, it was found that parenting patterns, lack of knowledge, easy access to pornographic media, attitudes of close friends towards sexuality, lack of religious attitudes, age, living without permissive parents, low socioeconomic status, teenagers who do not attend school is a major factor in the cause of unwanted pregnancies in adolescents. There are 6 articles that meet the inclusion criteria, namely the factors causing unwanted pregnancy in adolescents. Results: Based on the articles collected, it was found that parenting patterns, lack of knowledge, easy access to pornographic media, attitudes of close friends towards sexuality, lack of religious attitudes, age, living without permissive parents, low socioeconomic status, teenagers who do not attend school is a major factor in the cause of unwanted pregnancies in adolescents. There are 6 articles that meet the inclusion criteria, namely the factors causing unwanted pregnancy in adolescents. Results: Based on the articles collected, it was found that parenting patterns, lack of knowledge, easy access to pornographic media, attitudes of close friends towards sexuality, lack of religious attitudes, age, living without permissive parents, low socioeconomic status, teenagers who do not attend school is a major factor in the cause of unwanted pregnancies in adolescents.